Dinâmicas Territoriais na Zona Costeira do Estado do Pará, Amazônia Brasileira - Gilberto de Miranda Rocha; Daniel Araújo Sombra Soares; Sérgio Cardoso de Moraes (Confins)
This article aims to analyze the territorial dynamics in the coastal zone of the State of Pará, the Brazilian Amazon. In this study, we will focus attention on the identification of the main factors that determined the spatial structure, the transformations in the use and occupation of the territory over time and the factors that currently promote social change in the space in question. The analysis of the dynamism of the coastal zone along the historical process induces us to understand the spatial logics underlying each period, as well as allows us to identify the determinants of the current spatial configuration and its functionality for territorial planning. The objective of this work is to understand the spatial structures, the territorial dynamics and the vectors of development of the coastal area of Para.